Implementation of the soil health monitoring system to achieve better yield - S. R. Bhagyashree; Guddappa Halligudra; Anupama Sindagi; Madhu Nagaraj; C. Shyamala; Shaista Tarannum; R. Thailagavathy; T. R. Yashavantha Kumar (International Journal of Applied Power Engineering (IJAPE), 2026)
Agriculture is a fundamental pillar of the economy, particularly in developing countries where a significant proportion of the population depends on farming for their livelihood. Crop productivity is influenced by soil type and its changing chemical properties. A lack of understanding of soil health, crop-specific nutrient requirements, and the interaction between water and the environment often leads to inappropriate irrigation and fertilizer use. As a result, crops receive either excessive or insufficient nutrients, leading to reduced yields and the waste of water, energy, and other valuable resources. To address these issues, this paper presents an IoT-based soil health monitoring system that supports sustainable crop management. The proposed system integrates sensors to monitor key soil parameters such as temperature, humidity, soil moisture, and pH levels in real time. Based on the collected data, the system autonomously adjusts irrigation and environmental conditions to maintain soil health. This approach improves crop productivity, optimizes resource utilization, and promotes energy conservation in agricultural systems.